Morphological Features of Tongue in Domestic Cat Felis Catus - Khalil Ibrahim, Marwa; Hussein, Ashwaq Ahmed; Mutlak, Baydaa Hussein (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The current study aimed to identify the morphological description of the domestic cat tongue; thus for this purpose, five domestic cats of both sexes were collected from the local markets of Baghdad governorate, and then the animals were anesthetized and the tongue was removed from them. Fresh tongue samples were fixed using formalin (10%), and the preserved samples were dyed with methyl blue. The results showed that the tongue is an elongated organ divided into three regions: a somewhat flat rounded apex, this region contains a central depression called the middle groove. The second region is the lingual body region represents the largest region of the tongue, whereas its last region, called the root which has a lingual prominence on its dorsal surface. In addition, the dorsal surface of the tongue is covered by five types of lingual papillae, the most common of which are filiform papillae that spread over the entire dorsal surface of the tongue, while the presence of cylindrical papillae is limited to a specific area of the lingual body close to the apex. Moreover, the fungiform papillae spread between the filiform papillae and gradually increase in size towards the lingual root, while the presence of circumvallate papillae is limited to the lingual root and its number is 5 papillae. Finally, the foliate papillae are located on both sides of the lingual root, while the ventral surface of tongue is smooth without lingual papillae. In conclusion, the results of this study showed that the distribution pattern of the lingual papillae in the domestic cat differs from the rest of the other mammalians.